PARADIGMA KOMUNIKASI KRITIS: SUATU ALTERNATIF BAGI ILMU KOMUNIKASI - ', Yasir (Jurnal Ilmu Komunikasi, 2012)
Critical Communication Paradigm: An Alternative for Science Communication. Thispaper attempts to explain the process of dehumanization in the number of social reality and the developmentof science communication. To overcome this, a critical paradigm as a grand theory of communication isoffered as an option. As an alternative paradigm of this paradigm is expected to be able to free people fromthe cultural and social structures that contain elements of injustice, oppression, domination anddehumanization. This paradigm has the power to change what had happened to the science, theory, practicecommunication and social reality itself.